Alkenes Recent Advances, New Perspectives and Applications - Davarnejad, Reza (IntechOpen, 2021)
Alkenes, which have carbon-carbon double bonds, are chemicals and energy sources that play an important role in human life, including economics and the environment. This book examines the production and synthesis of alkenes, olefins, and polyolefins, as well as environmental issues faced during industrial production of these hydrocarbons. It also discusses eco-friendly and green separation techniques.